Local Wisdom in Play: Hand Puppets Made from Ilung as Alternative Media to Develop Early Childhood Skills - Nor Izzatil Hasanah (Muadalah, 2026)
Since before the 1990s, Ilung (water hyacinth) was used by village children around the river as a medium for playing with hand puppets, because at that time toys like Barbie were not yet available. This study aims to describe the process of making hand puppets from Ilung and the use of Ilung as an alternative educational medium in the form of simple hand puppets for micro role-play activities in early childhood education. This study is a qualitative descriptive study using observation, interview and documentation techniques to collect data. The subjects of this study were 1 parent and 2 children who often play with Ilung at home. The results show that hand puppets made of Ilung can be made with simple techniques and used as a creative role-play medium to develop child’s language skill. This approach combines local wisdom with innovative learning methods, resulting in affordable, environmentally friendly learning media, and introducing children to cultural values ​​and the surrounding environment. These findings serve as a reference for educators in developing learning media based on local resources.